SKRINING TUMBUH KEMBANG ANAK PADA SISWA KB INTAN PERMATA AISYIYAH MAKAMHAJI - Listiana Masyita Dewi; Muhamad Tegar Dwi Aji Pangestu; Feby Cindika Briliana; Faris Hasabi (LPPM Universitas Abdurrab, 2022)
Background: The golden period of growth and development of children occurs at the age of 0 to 6 years. Deviations in child growth and development needs to be detected so that intervention or stimulation can be given. Early detection (screening) of deviations in child development can be done using the DDST II (Denver Development Screening Test) method. KB Terpadu Intan Permata Aisyiah Makamhaji has slowly returned to using the face-to-face learning system. However, efforts to monitor the growth and development of the students have not been implemented yet. Objective: To obtain demographic information about the growth and development of students in KB Terpadu Intan Permata Aisyiah Makamhaji. Methods: Screening for the growth and development of students of KB Terpadu Intan Permata Aisyiah Makamhaji was carried out in 2 stages. The first stage is measuring the child's growth rate through measuring their weight and height to determine their BMI and adjusted for age. The second stage is the measurement of children's developmental achievements using the DDST II form and tool set. Results: Measurement of growth rate obtained 85% of students have very thin nutritional status and only 0.05% are classified as normal nutritional status. Measurement of developmental achievement found that 90% of students had normal development, while others were considered suspicious and unstable. The gross motor aspect is one aspect in which most students are considered advanced.Conclusion: The growth rate of students in KB Terpadu Intan Permata Aisyiah Makamhaji is still not in accordance with the age level, while the achievement of their development is quite good